Volodymyr Derzhavyn and the Artistic Ukrainian Movement - Stepan Khorob (Vasyl Stefanyk Precarpathian National University, 2017)
One of the most productive periods in the career of an outstanding emigration literary theorist Volodymyr Derzhavyn (1899-1964) was the time of his membership in the MUR (Mystetskyi ukrainskyi rukh - the Artistic Ukrainian Movement) in Bavaria, Germany from the mid to the end of the 1940s. The article highlights his theoretical debates with Yurii Sherekh (Shevelov) over the issue of style in Ukrainian diaspora literature.